(untitled) (Acta Scientiarum. Health Sciences, 2014)
The effects of chromium picolinate in Type 2 diabetic patients are investigated. Seventeen Type 2 diabetic patients were randomly divided into two groups. The experimental group received fiber-rich hypocaloric diet and chromium picolinate whereas the control group received fiber-rich hypocaloric diet and placebo. The chromium picolinate was offered twice a day at the dose of 100 Î¼g. Anthropometric data such as blood pressure, fasting glycemia and glycated hemoglobin (HbA1c) were measured and these parameters were evaluated again after 90 days. No difference was reported in rates of body weight, waist, hip, body mass index, blood pressure and fasting glycemia (Control vs. Experimental groups) after treatment. However, a decrease (p = 0.0405) of HbA1c occurred in the experimental group when the pre- and post-treatment rates were compared. HbA1c data showed that chromium picolinate improved the glycemic control in Type 2 diabetes.